Professional Self-Development of a Teacher of a Higher Education Institution: Interdisciplinary Aspect - Olesia Smolinska; Khrystyna Dzyubynska (Vasyl Stefanyk Precarpathian National University, 2020)
This article deals with the urgent problem of teacher's professional self-development at a higher educational institution, based on normative and acmeological aspects. In the process of achieving this goal - which is the study of the peculiarities of professional self-development in the terms of Ukrainian higher education in its cultural and historical context - the analysis of such problems, as the transformation of forms of consciousness into educational interactions; professional archetype of a teacher; the transformation of the content of professional self-development, was conducted. The given problem has practical meaning. It means that there are a number of objective factors, which influence the essence of a teacher's professional self-development, as a process, connected with the concept of lifelong education, and turn it into a component of the creation of professional identity. We came to the following conclusions: firstly, concerning the dual nature of professional and personal identity (real and imaginary, virtual), which is objectified in the cultural and educational space of the university; secondly, studying the peculiarities of the teacher's self-development,special attention should be paid to appropriate archetypes as culturally conditioned generalized patterns; thirdly, a change in the type of teacher's professional self-development is caused by both the transformation of the character of the person's identity and the change of archetype